Nucleotide sequence and functional analysis of the complete phenol/3,4-dimethylphenol catabolic pathway of Pseudomonas sp. strain CF600. - Shingler, V (1992)
The meta-cleavage pathway for catechol is one of the major routes for the microbial degradation of aromatic compounds. Pseudomonas sp. strain CF600 grows efficiently on phenol, cresols, and 3,4-dimethylphenol via a plasmid-encoded multicomponent phenol hydroxylase and a subsequent meta-cleavage pathway. The genes for the entire pathway were previously found to be clustered, and the nucleotide sequences of dmpKLMNOPBC and D, which encode the first four biochemical steps of the pathway, were determined. By using a combination of deletion mapping, nucleotide sequence determinations, and polypeptide analysis, we identified the remaining six genes of the pathway. The fifteen genes, encoded in the order dmpKLMNOPQBCDEFGHI, lie in a single operon structure with intergenic spacing that varies between 0 to 70 nucleotides. Homologies found between the newly determined gene sequences and known genes are reported. Enzyme activity assays of deletion derivatives of the operon expressed in Escherichia coli were used to correlate dmpE, G, H, and I with known meta-cleavage enzymes. Although the function of the dmpQ gene product remains unknown, dmpF was found to encode acetaldehyde dehydrogenase (acylating) activity (acetaldehyde:NAD+ oxidoreductase [coenzyme A acylating]; E.C.1.2.1.10). The role of this previously unknown meta-cleavage pathway enzyme is discussed.